HUBUNGAN RESIKO PEKERJAAN DENGAN KECELAKAAN KERJA PADA PETUGAS PEMADAM KEBAKARAN DINAS KOTA MEDAN - Sherina Putri Aulia; Siregar, Santy Deasy; Ginting, Johannes Bastira (Jurnal Kedokteran Ibnu Nafis, 2024)
Occupational accidents are incidents that cause damage to human beings, and awareness of the application of K3 can minimize the risk of accidents in the workplace. The aim of this study is to find out the relationship between job risks and work crashes in firefighters at the field city fire department. This study uses quantitative methods, using cross sectional approaches. The population used in this study was firefighters at the Fire Department of the City of Medan, with a sample of 63 firemen. The study found that there was no relationship between work behavior and work accidents, while there was a relationship between the work environment and the work accident in firefighters with a p-value of 0.207 for the behavioral variable, while the p-valued value of 0.018 for the working environment variable. The conclusion is that there is no relationship between behavior and workplace accidents, whereas there is a relationship between workplace and firefighting accidents. Recommendations for firefighters are expected to follow more regular physical and theoretical training to minimize the occurrence of work accidents and for the research site is expected to facilitate more APD in accordance with the number of officers who come down directly to extinguish the fire